An observational cross-sectional study of varied clinical manifestations of connective tissue disorders and their association with antinuclear antibodies in a tertiary care center - Rana Abdul Kadiru; Spandana P Hegde; Manjunath M Shenoy (Wolters Kluwer Medknow Publications, 2019)
Context: Connective tissue disorders (CTD) occur in 3-5% of the population. The advent of antibodies to extractable nuclear antigens (ENA) has become a reliable predictor to establish the diagnosis of CTD, subclassify patients into prognostic groups, and monitor disease activity. Aims: The aim of this study was to (a) study the frequency of cutaneous manifestations, systemic manifestations, and anti-ENA antibodies in CTD; (b) determine the association between systemic manifestations and ENAs; and (c) determine the association between cutaneous and systemic manifestations of CTD. Subjects and Materials: An observational cross- sectional study was conducted on 50 patients diagnosed to have CTD. The clinical profile and antibodies to ENA (ANA Profile) reports were retrieved and studied. Results: The major dermatological manifestations were skin tightness (36%), salt and pepper pigmentation (30%), Raynaud's phenomenon (28%), and malar rash (28%). The common antibodies seen were anti SS-A (36%), anti-UI-ribonucleoprotein (U1-RNP) (34%), anti-dsDNA (32%), and anti-Sm (24%). Patients with anti-Sm and anti-dsDNA antibodies had increased frequency of renal manifestations. A strong association with significant P values was seen between neurological manifestations and anti-Sm antibody, and cardiovascular manifestations and anti-RNP antibody. An association between gastrointestinal manifestations and malar rash as well as neurological manifestations and photosensitivity was also seen. Conclusions: ENA panel predicts systemic involvement, thus helping in the multidisciplinary management. Cutaneous manifestations of CTD can be an early predictor in giving a clue to impending systemic manifestations.